Heavy metals analysis and quality assessment in drinking water – Khorramabad city, Iran - Ghaderpoori, Mansour (Data Brief, 2017)
Continuous monitoring of drinking water quality is essential in terms of heavy metals and toxic substances. The general objective of this study were to determine the concentration of heavy metals in drinking water of Khorramabad city and to determine the water quality indices (The heavy metal pollution index and heavy metal evaluation index). According to the city map, 45 points were selected for drinking water sampling through the city distribution system. The results of this study showed that the average concentration of heavy metals such as Zn, Pb, Cd, Cr, and Cu were 47.01 μg/l, 3.2 μg/l, 0.42 μg/l, 5.08 μg/l, and 6.79 μg/l, respectively. The HPI and HEI (water quality indices) for Zn, Pb, Cd, Cr, and Cu were 46.58, 46.58, respectively. According to the indices, the city drinking water quality is good in terms of heavy metals.